The German Influence on the Reform of the Normal Schools for female and male Preceptors in South Central Chile, 1883-1920 - Mansilla Sepúlveda, Juan Guillermo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article studies the influence of the German pedagogy in the teachers training reform of the Normal Schools promoted by the liberal governments at the end of the 19th century in Chile. The visits of Valentín Letelier Madariaga and José Abelardo Núñez to Germany convinced them about the superiority of Germanic methods and the need to provide the Chilean pedagogy with a scientific status, in the image and likeness of Western European and positivist culture. This documentary theoretical analysis aims to understand the dynamics of the German ideological and cultural presence in the Nation-State project, thought and dreamed, by the oligarchical leading groups of Chile based on the formation of female and male preceptors. The method was qualitative-descriptive with a historiographic design developed from the methodological triangulation between primary and secondary sources. The results of this work can stimulate the interest to study an unexplored field in the Chilean educational research: the vast German influence at the beginning of the installation of the Normal School in South-central Chile.